Oxford international primary English student book: for grade 4 - Danihel, Emma; Hearn, Izabella (Oxford university press: Lahore, 2022)
Oxford international primary English provides an exciting route into developing literacy skills, including speaking, listening, reading and writing. Throughout this carefully levelled course, students of classes 1-6 can explore a wide range of fiction, non-fiction and poetry texts from around the world. This textbook series puts student's well-being at the heart of their learning experience.